Advantages and Disadvantages of Reconstruction - Budaházi, Árpád (Magyar Rendészet, 2019)
Since the 19th century, reconstruction was introduced to and was known to Hungarian criminal procedures. Since the very beginning, it has been used to replicate the event, phenomenon, action or any of their parts under the same circumstances as they could have actually happened. The results of reconstruction are expected to verify or confute the testimony of the witness or the defendant. Furthermore, it is also a measure of credibility investigations, whereas the proceeding authority is checking whether the actions could take place as suspected upon the available data. However, it is questionable, whether reconstruction holds any disadvantages besides its benefits; moreover, we must examine in this paper the reasons behind the rare practice of this evidentiary procedure. It must be further viewed in the paper if there is a correlation between its infrequent application and its legal background.